Development of bovine hydroxyapatite coating on TI6AL4V implant by plasma electrolytic oxidation / Adeleke Sakiru Adekunle - Adeleke Sakiru , Adekunle (2018)
Plasma electrolytic oxidation (PEO) is used to prepare bioactive hydroxyapatite ceramic coatings on light metals. The extensive literature reports on the bioactive hydroxyapatite-oxide coatings formed under a wide range of different electrical parameters and in various electrolyte concentrations. However, little work is available that investigates systematically the influence of hydroxyapatite concentration in the oxide film using a solitary sodium phosphate (NAP) electrolyte solution. In this present work, a single PEO process was used to produce film incorporating HA, and the aftermath effects of various HA concentrations in the oxide film on the Ti6Al4V alloy substrate were examined. The findings revealed that the oxide film was greatly influenced by the various hydroxyapatite particles. It was found that the amount of hydroxyapatite particles infiltrated into the coatings layer as well as the thickness and the surface roughness of the coating increased with increasing HA concentration. The porosity of the HA coatings indicated an inverse relationship with the concentration of HA particles in the NAP solution. The result also demonstrates that higher scratch adhesive strength was achieved using 1.5 g/L HA solution, producing a critical load of 2099 mN, while 0 g/L HA only produced a critical load of 1247 mN. The adhesion becomes independent of thickness when the concentration of HA exceeds 1.5 g/L. The failure of the coating was characterized by large periodic hemispherical chipping, while intermittent delamination was noticed with the coating embedded with HA particles. Due to the increasing demand to develop coatings with unique phase/elemental composition similar to hard bone tissues. The study also examined the coatings formed in a biologically friendly electrolyte containing natural bovine bone-derived HA (BHA) under a range of different voltage regimes, current density and time. The results indicated that the combination of a various voltage regime 225-325 V, current density of 500 mAcm-2 and deposition time of 5 mins produced a rough and porous surface coating. The surfaces of the coated layers were filled with anatase-TiO2, cubic-MgO and hexagonal-BHA particles. The coatings formed in a newly developed bovine-bone derived-HA revealed an additional MgO phase in the coating layer. A film-to-substrate adhesion strength of 2010 mN was achieved. Moreover, the PEO-BHA coatings significantly improved the wear performance of titanium alloy. However, the coefficient of friction (COF) for the coating at 325 V is almost the same with the one produced at 300 V due to porous layer of the coating formed at 325 V. A comparative study on the in vitro corrosion and bioactive performance of commercial hydroxyapatite (CHA) and BHA coatings was also studied. The corrosion and bioactivity properties were evaluated using potentiodynamic polarization and simulated body fluid, respectively. The electrochemical tests demonstrated that the oxide coatings containing different phases possess sufficient protection efficiency. The apatite layer formed on the PEO-BHA coating was more and denser than that of PEO-CHA coating, whereas apatite structure was completely formed on the two surfaces.